2013
DOI: 10.1371/journal.pone.0059307
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Antiviral Activities of Chicken Interferon α (ChIFN-α) and ChIFN-β are Related to Distinct Interferon-Stimulated Gene Expression

Abstract: Chicken interferon α (ChIFN-α) and ChIFN-β are type I IFNs that are important antiviral cytokines in the innate immune system. In the present study, we identified the virus-induced expression of ChIFN-α and ChIFN-β in chicken fibroblast DF-1 cells and systematically evaluated the antiviral activities of recombinant ChIFN-α and ChIFN-β by cytopathic-effect (CPE) inhibition assays. We found that ChIFN-α exhibited stronger antiviral activity than ChIFN-β in terms of inhibiting the replication of vesicular stomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 63 publications
1
46
0
Order By: Relevance
“…Cell samples were collected at 0, 4, 8, and 12 h p.i. (hours post-infection) for RNA isolation as previously described [31]. The RNA samples were treated with DNase I (TaKaRa) at 37°C for 30 min.…”
Section: Rna Extraction and Quantification By Real-time Pcrmentioning
confidence: 99%
“…Cell samples were collected at 0, 4, 8, and 12 h p.i. (hours post-infection) for RNA isolation as previously described [31]. The RNA samples were treated with DNase I (TaKaRa) at 37°C for 30 min.…”
Section: Rna Extraction and Quantification By Real-time Pcrmentioning
confidence: 99%
“…The antiviral activity and anti-proliferation activity of IFNβ is lower than most of the IFNαs, and the antiviral activity of IFNα-evoluted IFNs is stronger than that of IFNκ and IFNεs (Sang et al, 2010;Lavoie et al, 2011). The ISGs that IFNβ induces tend to regulate host immunoreactions, while IFNα tends to induce antiviral proteins, such as 2′-5′ OAS and PKR (Qu et al, 2013). This may be caused by the different ways that they interact with IFN receptor subunits.…”
Section: Research Articlementioning
confidence: 99%
“…In addition, the pretreatment of cells with interferon-β can sometimes enhance the IFN yield (an effect called priming) (Honda et al, 2006). The Qu et al (2013) found that the adding of ChIFN-β (chicken IFN-β) increase the IFN at the beginning of treatment, reaching peak level at 12 hours and then decreased. The positive control clearly had the highest gene expression at 12, 24, 36 hpi of M gene but decline at 48 hpi due to the damage of infected cells as mention by Kumar et al (2013).…”
Section: Qrt -Pcrmentioning
confidence: 99%